PENINGKATAN KREATIVITAS GURU DI ERA 4.0 MELALUI PEMANFAATAN TEKNOLOGI SEBAGAI MEDIA PEMBELAJARAN KREATIF DAN EDUKATIF - Dyah Ayu Apriliyana; Ida Dwijayanti; Diah Saraswati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to examine the positive impact of using the web-based application Assemblr Edu in the process of creating teaching materials to enhance teacher creativity in the advanced 4.0 era. The research method employed is a mixed-method approach, combining qualitative and quantitative techniques to provide a more comprehensive understanding. The results show that the use of Assemblr Edu significantly improves teachers' competencies in facing the 4.0 era and helps teachers feel more confident when teaching in the classroom by utilizing a media that is crucial in modern education. A total of 66% of respondents agreed or strongly agreed with the benefits of Assemblr Edu as a creative and educational teaching media. This study underscores that utilizing Assemblr Edu media has a significant impact on improving teaching quality. Therefore, the author recommends that in the future, teachers continue to integrate Assemblr Edu as a tool for creating creative and educational teaching materials to create interesting learning